If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -1(6x + 9) = 7x + -29 Reorder the terms: 9x + -1(9 + 6x) = 7x + -29 9x + (9 * -1 + 6x * -1) = 7x + -29 9x + (-9 + -6x) = 7x + -29 Reorder the terms: -9 + 9x + -6x = 7x + -29 Combine like terms: 9x + -6x = 3x -9 + 3x = 7x + -29 Reorder the terms: -9 + 3x = -29 + 7x Solving -9 + 3x = -29 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -9 + 3x + -7x = -29 + 7x + -7x Combine like terms: 3x + -7x = -4x -9 + -4x = -29 + 7x + -7x Combine like terms: 7x + -7x = 0 -9 + -4x = -29 + 0 -9 + -4x = -29 Add '9' to each side of the equation. -9 + 9 + -4x = -29 + 9 Combine like terms: -9 + 9 = 0 0 + -4x = -29 + 9 -4x = -29 + 9 Combine like terms: -29 + 9 = -20 -4x = -20 Divide each side by '-4'. x = 5 Simplifying x = 5
| 5m-4=3(m+6) | | 4a-7=7(a+1)+14a+6 | | t+30=1 | | 5-2(2m+3)=15 | | 2(10x+3)=5(4x-7) | | -23=5k+7k | | 0.6x=0.4x+50 | | 2(5-3x)=9-6x | | -7.6=5.3+x+7.34 | | 4x+6(x+40)=180 | | 6t-32=7t-50 | | 5c=c+52 | | 3(2x-8)=2(3x+8) | | 2(sqrt(x))-5=x | | 7x-1=2x-3 | | 5-3x=3x-25 | | 527=31n | | 2x-3=6+2x | | -80.2-9x=1.7 | | 10x-75=51+4x | | o=5-(2x-17) | | x+3.07+2.5=1.8 | | -80.2-9x=-21.9 | | 10a+55b= | | 3x+7-9x=-11 | | x+43=87 | | x+5=1.5x+2.5 | | 10f+2(5f+8)=-10f-4(2f-30) | | 5d+9=24 | | 2=17 | | 8ex=7 | | p*(q+r)=qp+pr |